Interactive Psychometrics for Autism With the Human Dynamic Clamp: Interpersonal Synchrony From Sensorimotor to Sociocognitive Domains - Baillin, Florence; Lefebvre, Aline; Pedoux, Amandine; Beauxis, Yann; Engemann, Denis A.; Maruani, Anna; Amsellem, Frédérique; Kelso, J. A. Scott; Bourgeron, Thomas; Delorme, Richard; Dumas, Guillaume (Frontiers in Psychiatry, 2020)
The Human Dynamic Clamp (HDC) is a human-machine interface designed on the basis of Coordination Dynamics for studying realistic social interaction under controlled and reproducible conditions. Here, we propose to probe the validity of the HDC as a psychometric instrument for quantifying social abilities in children with Autism Spectrum Disorder (ASDs) and neurotypical development. To study behavioral synchrony with the HDC, we derived five standardized scores following a gradient from sensory-motor and motor to higher socio-cognitive skills in a sample of 155 individuals (113 with ASDs, 42 typically developing participants; aged 5 to 25 years; IQ>70). Regression analyses was performed using normative modeling on global scores according to four sub-conditions (HDC behavior "cooperative/competitive", human task "in-phase/anti-phase", diagnosis and age at inclusion). Children with ASDs had lower scores than controls for motor skills. HDC motor coordination scores were the best candidates for stratification and diagnostic biomarkers according to exploratory analyses of hierarchical clustering and multivariate classification. Independently of phenotype, socio-cognitive skills increased with developmental age, while being affected by the ongoing task and HDC behavior. Weaker performance in ASDs for motor skills suggests convergent validity of the HDC for evaluating social interaction. Results provided additional evidence of a relationship between sensory-motor and socio-cognitive skills. HDC may also be used as a marker of aging of socio-cognitive skills during real-time social interaction. Through its standardized and objective evaluation, the HDC not only represents a valid paradigm for the study of interpersonal synchrony but also offers a promising, clinically relevant psychometric instrument for the evaluation and stratification of socio-motor dysfunctions.